DEGRADASI DAN SISTEM PENGELOLAAN LAHAN DI DAERAH ALIRAN SUNGAI TULIS - Kusbiantoro, Ari; Awang, San Afri; Maryudi, Ahmad; Gunawan, Totok (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2015)
As a natural component, land is considered to be very essential factor of watershed system, as well as plant and human life. In fact, improper land using leads to land degradation that causes negative effect to watershed ecosystem. Therefore, the right land management system is needed. The objective of the research is to study land degradation carried by social activities in Tulis Watershed. The parameters under study were social-economic, land management, and biophysical in Tulis Watershed. The parameters were obtained by using observation and document study. Theoretic analysis was done to know relation between social activity in land using and land degradation of Tulis Watershed. Social theories were used as basic theory in structure and society’s behavior concept in land management. Meanwhile, land degradation theories were applied as basic theory in analyzing land-use system. Land use system of Potatoes monoculture plantation system used by most people in Tulis Watershed increased land degradation. Therefore, proper land management and social norms obedience were expected be able to decrease land degradation, so they benefited the societies living in social, economy, and environment. In other words, land management system had to assure sustainable watershed ecosystem and increase society’s welfare in Tulis Watershed. Key words: Watershed, degradation, social activity, land management, potatoes